Stable Strontium Isotopic Compositions of River Water, Groundwater and Sediments From the Ganges–Brahmaputra–Meghna River System in Bangladesh - Yoshimura, Toshihiro; Wakaki, Shigeyuki; Kawahata, Hodaka; Hossain, H. M. Zakir; Manaka, Takuya; Suzuki, Atsushi; Ishikawa, Tsuyoshi; Ohkouchi, Naohiko (Frontiers in Earth Science, 2021)
The Sr isotopic composition of rivers and groundwaters in the Bengal Plain is a major contributor to the global oceanic Sr inventory. The stable strontium isotope ratios (δ88Sr) provide a new tool to identify chemical weathering reactions in terrestrial water. In this study, we investigated the spatiotemporal variations of δ88Sr in samples of river water, bedload sediment, and groundwater collected from the Ganges–Brahmaputra–Meghna drainage basin in Bangladesh, which is known to strongly influence the 87Sr/86Sr ratio in seawater. The average δ88Sr values of waters of the Ganges, Brahmaputra, and Meghna rivers were 0.269, 0.316, and 0.278‰, respectively. Our data showed little difference between seasons of high and low discharge. The δ88Sr values measured in sequential leaching fractions of sediments varied from –0.258 to 0.516‰ and were highest in the silicate fraction, followed in turn by the carbonate fraction and the exchangeable fraction. Both 87Sr/86Sr and δ88Sr of these waters are primarily controlled by the inputs of Sr in weathering products from the Bengal Plain and Sr from the Himalayan rivers (Ganges and Brahmaputra). Values of δ88Sr and Sr/Ca were higher in the Brahmaputra River than in the Ganges River, a difference we attribute to greater input from silicate weathering. The variations of δ88Sr and 87Sr/86Sr were greater in groundwater than in river waters. Mineral sorting effects and dissolution kinetics can account for the large scatter in 87Sr/86Sr and δ88Sr values. The depth profile of δ88Sr showed wide variation at shallow depths and convergence to a narrow range of about 0.31‰ at depths greater than 70 m, which reflects more complete equilibration of chemical interactions between groundwater and ambient sediments owing to the longer residence time of deeper groundwater. We found that δ88Sr values in the groundwater of Bangladesh were almost identical to those of river water from the lower Meghna River downstream of its confluence with the Ganges–Brahmaputra river system, thus confirming that the δ88Sr composition of the groundwater discharge to the Bay of Bengal is very similar to that of the river discharge.